(untitled) (Journal of Medical & Health Sciences Review, 2025)
COVID-19’s severity links to out-of-control inflammatory responses. The Neutrophil-to-Lymphocyte Ratio (NLR) and Lymphocyte-to-C- Reactive Protein Ratio (LCR) stand in for systemic inflammation and immune status. To compare NLR, LCR and inflammatory markers among vaccinated vs non-vaccinated. An observational cross-sectional study of 256 subjects (156 unvaccinated, 100 vaccinated). Demography, symptoms and laboratory parameters were compared with the independent t-test, chi-square and ANOVA. Vaccinated individuals showed significantly lower NLR (2.41 ± 1.12 vs 6.52 ± 3.84, p<0.001), higher LCR (2.94 ± 1.52 vs 0.83 ± 1.21, p<0.001), and lower CRP (0.82 ± 0.31 vs 14.23 ± 10.51 mg/L, p<0.001). Against unvaccinated 84.4% a rare count 3% vaccinated people developed the symptoms (p<0.001) with cohen’s d range 1.42 to 1.89. The large size data were managed precisely. Inflammatory markers restrain the value of immunization during the covid, the study people those were immunized showed up lower or mild levels in their blood resulting the stable immune system.